2003
DOI: 10.1074/jbc.m304663200
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Heat Shock Factor (HSF) 2A Stimulates HSF1-induced Transcription during Stress

Abstract: Heat shock factor 2 (HSF2) belongs to a family of structurally related transcription factors, which share the property of binding to heat shock elements in the promoters of hsp molecular chaperone genes. However, unlike HSF1, which is essential for hsp gene transcription, the cellular functions of HSF2 are not well known. Here we show that human HSF2, although an ineffective activator of the hsp70 promoter in vitro and in vivo in the absence of stress, participates in the activation of the hsp70 promoter by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 50 publications
4
73
0
Order By: Relevance
“…By forming heterocomplexes with different compositions, a gradient of transactivation could be achieved. The transcriptional capacity of HSF1 in reporter assays is stronger than that of HSF2, and functional interaction on the level of transactivation had been studied previously only in reporter assays (37,56). Our results regarding the role of HSF2 in the heat-induced activation of hsp70 promoter are in line with the reporter assays performed by He et al (37), who reported that overexpression of the HSF2-␣ isoform in the presence of HSF1 enhanced heat-induced hsp70BЈ promoter activity.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…By forming heterocomplexes with different compositions, a gradient of transactivation could be achieved. The transcriptional capacity of HSF1 in reporter assays is stronger than that of HSF2, and functional interaction on the level of transactivation had been studied previously only in reporter assays (37,56). Our results regarding the role of HSF2 in the heat-induced activation of hsp70 promoter are in line with the reporter assays performed by He et al (37), who reported that overexpression of the HSF2-␣ isoform in the presence of HSF1 enhanced heat-induced hsp70BЈ promoter activity.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to HSF1, HSF2 has been shown to translocate to punctuated structures in the nucleus of heat-shocked HeLa cells (35). Subsequently, we observed that during heat shock, HSF1 and HSF2 co-localize in the nuclear stress bodies, and a direct interaction between HSF1 and HSF2 during both control and heat shock treatment has been demonstrated (36,37). Reporter assays have suggested that HSF2 is able to potentiate HSF1-mediated transactivation (37).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…HSF2 has two isoforms due to splicing: HSF2A and HSF2B [26]. HSFs have a binding domain, a helical trimerization surface, and a short conserved element.…”
Section: Heat Shock Transcriptional Factorsmentioning
confidence: 99%